Analysis of the Implementation of PSAK 72 on the Current Ratio, Debt to Asset Ratio , and Net Profit Margin in Manufacturing Companies in the Basic Materials Sector Listed on the IDX for the 2015-2024 Period - Mohamad Faizun (Cahaya Abadi Publisher, 2026)
This study aims to analyze the impact of the transition from PSAK 34 (Construction Contracts) and PSAK 23 (Revenue) to PSAK 72 (Revenue from Contracts with Customers) on the financial performance of basic materials sector manufacturing companies listed on the Indonesia Stock Exchange during 2015–2024. The research uses a comparative approach by examining company performance before and after the mandatory implementation of PSAK 72 in 2020. PSAK 72 replaces previous standards by introducing a unified revenue recognition model based on five stages that adopt IFRS 15 principles. The sample consists of 90 financial statements selected through purposive sampling. Since the data were not normally distributed, the study applied the Wilcoxon Signed Rank Test using SPSS version 31 to examine differences in financial performance. The analysis focuses on liquidity measured by the Current Ratio (CR), solvency measured by the Debt to Asset Ratio (DAR), and profitability measured by the Net Profit Margin (NPM). The results indicate that CR shows a significant difference after the implementation of PSAK 72 with an Asymp. Sig. (2-tailed) value of 0.002, while DAR shows no significant difference with a value of 0.315, and NPM also shows no significant difference with a value of 0.969. These findings suggest that PSAK 72 mainly affects liquidity due to account reclassification, including contract assets. Therefore, investors are encouraged to carefully evaluate current asset components, while company management is advised to improve contract disclosure transparency to reduce information asymmetry and maintain stakeholder confidence during the accounting standard transition.